Hypersensitivity to Vitamins with a Focus on Immediate-Type Reactions: Food or Drug Allergy? - Calogiuri, Gianfranco; Garvey, Lene H.; Nettis, Eustachio; Casciaro, Francesco; Alsowaidi, Shirina; Foti, Caterina; Vacca, Angelo (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Vitamins are essential substances for normal cell functions, growth, and development. However, they cannot be produced by the human organism, so intake must be through the diet. Vitamin deficiency causes the onset of different diseases, ranging from pellagra to pernicious anemia, which can be corrected by reintroducing the missing vitamin form. To supply the right amount of vitamins to the body, every vitamin naturally occurring in foodstuff has been identified, extracted and synthetically produced, thus allowing either food fortification with these compounds or their pharmaceutical production. Furthermore, the increased importance attributed nowadays to body wellness and the pursuit of a permanent status of health at all costs has greatly encouraged a high consumption of vitamin supplements in modern society, since vitamin megadoses may be responsible for adverse or toxic effects. However, excessive vitamins can induce hypervitaminosis. In the USA, a national survey confirmed that 52% of adult Americans take at least one or more supplement products, vitamins and minerals being the most popular supplements in that country. Although vitamins are widespread natural substances, they may induce immediate or delayed type hypersensitivity reactions. Such adverse events are still underestimated and poorly recognized because only single cases have been reported in the literature, and no general review has yet investigated the mechanisms underlying sensitization to each vitamin, the diagnosis, and the management strategies adopted for vitamin hypersensitivity. Although delayed-type reactions to different vitamins are described in the literature, in our review, attention has been focused mainly on immediate- type reactions. Due to the importance of vitamins, further information regarding the above aspects (pathomechanisms, diagnosis and management) would be highly desirable to focus the state of the art on this particular, underestimated form of allergy, thus increasing allergists' awareness on these elusive hypersensitivity reactions.
Keywords: Vitamins